GAMBARAN MOTIVASI BELAJAR SISWA SELAMA PEMBELAJARAN DARING - Ana Fitriani; Rukiana Novianti Putri; Miranda Gunawan (JBKPI: Jurnal Bimbingan dan Konseling Pendidikan Islam, 2022)
Abstact: Education system in Indonesia is experiencing new challenges due to the Covid-19 virus outbreak, which has caused the entire learning system in educational institutions to be transferred to online learning methods. transferred to online learning system certainly has an impact on learning motivation of student, because students will feel the difference and change in the atmosphere in the online learning process.This study aims to explain in detail how the objective motivational conditions experienced by students in online learning during the Covid-19 pandemic. This study uses a qualitative approach by using non-probability sampling, namely the purposive sampling technique. The results showed that there was a decrease in learning motivation in junior high school students who participated in online learning. Characterized by a lack of desire and interest to succeed in learning; lack of motivation and need for learning; do not understand the hopes and aspirations of the future; lack of appreciation in learning; students have not been able to capture the interesting atmosphere that causes the learning process from home to be meaningful and the learning environment is less conducive.Keywords: Learning Motivation, Online Learning